Analisis Keterampilan Mengajar Menjelaskan Mahasiswa PGSD Semester VI Pada Mata Kuliah Pembelajaran Mikro - Nugrahanie Candra Maulidya (Jurnal Dharma PGSD, 2021)
The purpose of this study was to determine the basic teaching skills, namely the explaining skills mastered by the sixth semester students of class B PGSD Academic Year 2020/2021 University of Muhammadiyah Purworejo. There are three stages carried out in this research, namely the planning stage, the implementation stage, and the evaluation stage with quantitative research methods. At the planning stage, students make a Learning Implementation Plan (RPP) which will be used for practice. At the implementation stage, students carry out micro learning practices using the lesson plans that have been made. At the evaluation stage, when students practice teaching, other students will conduct an assessment using a questionnaire. Based on the results of data analysis, it shows that the skills of explaining PGSD students in semester VI class B for the Academic Year 2020/2021 at the University of Muhammadiyah Purworejo are in good criteria.